Chloe. 5, Carnival party - Tessier, Greg (Charmz, 2020)
After Chloe returns from her grandmother's, she finds her best friend has to go away for a week and her father has taken time off from work to do an exhausting list of activities with Chloe and her brother. Chloe takes a break to help with the neighborhood carnival, but things don't go as planned. Fortunately, her Uncle Steve is there to save the day. Then, Chloe struggles to adjust to the arrival of a British foreign exchange student staying with her family for a week.